Impact of Workplace Spirituality on Corporate Financial Performance - George, A. P.; Joji Alex, N. (Prabandhan: Indian Journal of Management, 2013)
This paper examines the perception of employees with regard to Workplace Spirituality and their perceived effect on Corporate Financial Performance. The findings of the study confirm a weak positive correlation between Workplace Spirituality and Corporate Financial Performance. The results indicate that Transcendence, Organizational Values, Individual and the Organization are the significant sub-dimensions of Workplace Spirituality that impact Corporate Financial Performance. The effects of Age, Gender, and Work Experience on Workplace Spirituality are also examined, with Gender difference making no impact. Age and Work Experience have an effect on Workplace Spirituality. Organizations need to do a lot more to align employees with organization values, so as to create a desired connect between Workplace Spirituality and Corporate Financial Performance.